Unusual Surgical Repair of Bronchoesophageal Fistula Following Esophagectomy - Predrag Sabljak; Ognjan Skrobic; Aleksandar Simic; Keramatollah Ebrahimi; Dejan Velickovic; Vladimir Sljukic; Nenad Ivanovic; Milica Mitrovic; Jelena Kovac (Diagnostics, 2024)
Radical esophagectomy remains the only potentially curative option in the treatment of esophageal cancer. However, this procedure is burdened with high morbidity and mortality rates, even in high-volume centers. A tracheo- or bronchoesophageal fistula (TBF) is rare but is one of the most difficult life-threatening complications following an esophagectomy for cancer treatment. Several classifications have been proposed regarding the localization of a TBF, its etiology, and the timing of its occurrence; hence, no classification is universally accepted. However, one of the most common etiological explanations for the formation of a TBF is a prior esophagogastric anastomotic leak. Treatment options include a conservative approach, which usually combines several endoscopic methods. Surgical treatment is directed towards fistula closure with direct suturing or, more often, the usage of pediculated flaps. Here, we present a patient with late TBF following a minimally invasive esophagectomy, which was surgically solved in an atypical way. We believe that this type of repair may be useful in patients in whom pedunculated flaps are not an option.